INKUBATOR KOTA - Marcellus Rafi; Agustinus Sutanto (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2019)
Social relation in human life fades subconsciously. Millennial which known for its tendency to always collaborate, is also not even try to synergize the compartmentalized way of life in a contrasted social-economic class. Even architects, most prefer to wrestle with fantastic designs rather than inovate the social interrelation. As a result, the city of Jakarta is filled with magnificent buildings with the principle of "Follow Finance Form". Responding to the issue, this project has a vision to see architecture from another perspective by putting forward the idea of "Sustainability in Society". Through research methods, 'Spatial Agency' and 'Everyday Urbanism', accompanied by a design method 'Hybridization of Architectural Programming'; The type of building is expected to be able to represent the sensitivity of an architect in seeing socio-spatiality with the depth of thinking. The content is correspondingly which consists of: public space, food market, community learning space, and living food farming. The four programs emerged from research results and methodologies, based on collaborative and synergy principles, become a  prototype of new city elements integrated with old elements around it. Able to contribute fully to the community to foster a balance between the natural environment that has been dominated and contaminated by manmade environment. The results of this project show that with the sharpness of thinking and sensitivity, architecture can contribute to the efforts of human welfare in different social and economic conditions while maintaining environmental sustainability for the better sustainability of the city in the future.AbstrakKeterhubungan sosial dalam kehidupan manusia semakin memudar dalam alam bawah sadar. Generasi Milenial yang dikenal dengan kecenderungan selalu berkolaborasi, pun tidak acuh untuk menyinergikan berbagai golongan ekonomi-sosial yang kontras. Begitpun arsitek, sebagian besar lebih memilih untuk menggeluti desain yang fantastis dengan bentukan yang melintir daripada interelasi terhadap sosial. Alhasil Kota Jakarta saat ini yang dipenuhi dengan bangunan pencakar langit dan mal megah dengan asas “Form Follow Finance”. Menanggapi isu tersebut, proyek ini memiliki visi untuk melihat arsitektur dengan mengedepankan ide “Sustainability in Society”. Melalui metode riset ‘agen keruangan’ dan ‘keseharian berurbanisme’, disertai metode desain ‘Hybridization of Architectural Programming’; Jenis bangunan yang dirancang diharap mampu merepresentasi kepekaan seorang arsitek dalam melihat socio-spatialitas dengan kedalaman berpikir yang dapat dipertanggungjawabkan. Hingga doperoleh kontent ruang yang terdiri dari: Public space, food market, community learning space, dan living food farming. Keempat program tersebut muncul atas hasil penelitian dan metodologi yang didasari atas prinsip kolaboratif dan sinergi, menjadi sebuah ‘prototipe’ elemen kota baru yang terintegrasi dengan elemen lama disekelilingnya. Mampu berkontribusi bagi masyarakat untuk mengupayakan keseimbangan antara lingkungan alam yang sudah terdominasi dan terkontaminasi oleh lingkungan buatan. Hasil proyek ini menunjukan bahwa dengan ketajaman berpikir dan kepekaannya, arsitektur dapat turut serta berkontribusi dalam mengupayakan kesejahteraan manusia dalam sosial dan ekonomi yang berbeda sekaligus menjaga kelestarian lingkungan demi lebih baiknya keberlangsungan kota di masa mendatang.